2012
DOI: 10.1249/mss.0b013e31822a2df0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wheel and Hand-Rim Size on Submaximal Propulsion in Wheelchair Athletes

Abstract: A greater power requirement owing to a greater rolling resistance in 24-inch wheels increased the physiological demand and magnitude of force application during submaximal wheelchair propulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…This is in line with Guo et al (2006) 16 who reported that the work that was done during a full propulsion cycle was significantly higher when a larger hand rim was used, although this result was found in able bodied participants. It has also been found that smaller wheels resulted in a greater rolling resistance and, therefore, an increased physiological demand and that the performance on a 20-meter sprint was better with a 65 cm wheel compared to a 59 cm wheel 17,9 . Although wheel diameter itself was not included as predictor in the models, wheel axis height and hand rim diameter were highly correlated with wheel diameter (r=.76 and r=.89, respectively; see also the correlations between predictor variables in the supplemental material II).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with Guo et al (2006) 16 who reported that the work that was done during a full propulsion cycle was significantly higher when a larger hand rim was used, although this result was found in able bodied participants. It has also been found that smaller wheels resulted in a greater rolling resistance and, therefore, an increased physiological demand and that the performance on a 20-meter sprint was better with a 65 cm wheel compared to a 59 cm wheel 17,9 . Although wheel diameter itself was not included as predictor in the models, wheel axis height and hand rim diameter were highly correlated with wheel diameter (r=.76 and r=.89, respectively; see also the correlations between predictor variables in the supplemental material II).…”
Section: Discussionmentioning
confidence: 99%
“…Wheelchair design has been repeatedly shown to influence propulsion in both daily living and sport [2,3], with these design parameters including seat height, depth, and angle [2,4], as well as camber [5] and wheel diameter [6]. However, the selection of optimal settings for these parameters is difficult due to the trade-off between performance factors, and the effects of these parameters being highly individualised due to differences in physical activity limitations of athletes in the sport.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the new test situation becomes more realistic in terms of simulating everyday scenarios. 2 Different possibilities of physical activity and sport for disabled individuals include the practice of wheelchair basketball, which has been investigated through a number of different scientific studies, including the assessment of physiological aspects, 8,9-10 nutritional factors, 11 kinematic features [12][13] and injuries. 14,15 When considering how athletes use wheelchairs for movement during a game, the function of the trunk has become one of the main parameters for the verification of functional capacity, including one of the main factors used in the class evaluation of the athlete.…”
Section: ' Introductionmentioning
confidence: 99%
“…These movements include trunk stability, sitting balance and trunk movement in the horizontal, frontal and sagittal planes, such as pushing and handling the wheelchair, dribbling, passing, shooting and rebounding the ball. 8 In the matter of postural balance, the literature contains studies conducted on a balance board in order to measure seated postural stability in individuals with disabilities; 6,[13][14][15][16][17] this is because individuals with SCI use different postural strategies to control sitting balance during the execution of task. 6,18 For wheelchair athletes, trunk balance is crucial for movement and the performance analysis of the trunk with respect to postural balance is a basic parameter for functional evaluation.…”
Section: ' Introductionmentioning
confidence: 99%